Award - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The 'Plant and Environment Protection' Association makes an annual award of 5,000 10,000 FF to researchers between 18 and 35 years old. To be eligible, such work (whether it be personal research, a bibliographic study or a project undertaken in the...